Kejahatan Narkoba: Penanggulangan, Pencegahan dan Penerapan Hukuman Mati - Dewi Iriani (Justicia Islamica, 2015)
Basically, drug crime is a form of extra ordinary crime. Of course, it needs joint steps in combating it. All parties should continue to be aware of drug trafficking. The war on drugs must involve all components of the nation because drugs are an extra ordinary crime. Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semisynthetic, which can cause a decrease or change in consciousness, loss of taste, reduce to eliminate pain, and can cause dependence, which is divided into groups as attached in Law Number 35 of 2009 concerning Narcotics.